Effectiveness of aromatherapy massage on the stress of the surgical center nursing team: a pilot study - Montibeler, Juliana [UNESP]; Domingos, Thiago da Silva [UNESP]; Braga, Eliana Mara [UNESP]; Gnatta, Juliana Rizzo; Sato Kurebayashi, Leonice Fumiko; Kurebayashi, Alberto Keidi (Univ Sao Paolo, 2018)
Objective: To verify the effectiveness of aromatherapy with essential oils of lavender (Lavandula angustifolia) and geranium (Pelargonium graveolens) associated with massage for stress relief of a nursing staff of the surgical center through evaluation of biophysiological and psychological parameters. Method: Pilot study, controlled and randomized clinical trial performed with the nursing team of a surgical center of a teaching hospital in the interior of the state of Sao Paulo. The intervention comprised six aromatherapy massages with essential oils diluted in neutral cream at concentration 1% each. Heart rate and blood pressure levels were measured before and after each massage session. The Work Stress Scale (WSS) and the List of Stress Symptoms (LSS) were applied before and at the end of the intervention. Statistical analysis was performed with the paired t-test and chi-square test, 95% confidence interval and p <0.05. Results: There was a statistically significant reduction in heart rate and blood pressure levels after massage sessions. Conclusion: The use of aromatherapy has demonstrated effectiveness for lowering biophysiological parameters of the surgical center nursing staff Brazilian Registry of Clinical Trials: RBR-6mgqn3.
Keywords: Aromatherapy; Burnout; Professional; Nursing; Team; Surgicenters; Operating Room Nursing